From Yucatán to the Court: Defenders of Indians, attorneys of the Spanish councils and legal process in the 16th century - Cunill, Caroline (2020)
The province of Yucatan has been often described as a Spanish empire’s periphery, not only because of its farness from the Courts (of Mexico and Spain), but also because of its conquest’s incompleteness, since extensive territories remained out of the colonial control for centuries. However, in the sixteenth century the Defensores (or advocates) of the Indians, as well as the Procuradores (or representatives) of the local Spanish towns maintained a close relationship with both the Mexican Court and the Council of the Indies. This article examines those actors’ travels, as well as the circulation of the documents they produced in order to determine the differential impact of those two factors on the production of imperial law. Special attention will be paid to the strategies aimed at interfering with the free circulation of persons and documents across the empire and its impact on the enactment of decrees related to the indigenous people of Yucatan.